AB0149 Associations of Anti Nucleosome Antibody in Systemic Lupus Erythematosus in India. (15th July 2016) - Gupta, N.; Doss, J.K.; Mohan, H.; Nair, A.; Sebastian, T.; Danda, D.
Abstract : Background: Nucleosomes are basic elements of chromatin and are considered to be the major antigens in the pathophysiology of systemic lupus erythematosus (SLE). Objectives: This study aimed to look for associations between anti nucleosome antibodies and clinical and laboratory parameters in SLE Methods: This retrospective study was done in department of Clinical immunology & Rheumatology in Christian Medical College, Vellore, India. Patients with SLE by SLICC 2012 criteria between March 2013 and September 2015 subjected to anti nucleosome antibody test formed the study cohort. A cut off of ≥20 U/ml by ELISA was defined as per manufacturer's (Euroimmune, Germany) instructions. Associations of anti nucleosome antibody with clinical and laboratory parameters in SLE was studied. Results: Anti nucleosome antibody was available for 238 patients with SLE. Mean age of the patients was 28.98±9.01 years with male to female ratio of 17: 221. Median disease duration was 8 (5–12) months prior to doing this test. Positive titers of anti nucleosome antibody (≥20 U/ml) were noted in 107 patients (46.5%). Renal involvement was seen in 134 (56.3%) patients. Univariate analysis reflected raised anti-c1q antibody, ESR, urinary protein creatinine ratio (UPC), anti dsDNA antibody, SLE disease activity index (SLEDAI), renal SLEDAI, low C3 and C4 as significant association of elevated anti nucleosome antibody levels. No significant association with arthritis, serositis, major infections, serositis, anti-phospholipid antibodies, autoimmune hematological cutaneous, neuropsychiatric, cardiovascular, respiratory, vasculitic and gastrointestinal manifestation was present. Multivariate regression analysis showed that raised anti-c1q antibodies and DsDna were associated with raised anti nucleosome antibody with odds ratio of 17.46 (95 CI: 1.46–213.86, p=0.02) and 82.94 (95 CI: 3.62–189.93, p=0.006) respectively. Conclusions: As per literature search, this is the largest single centre study of anti nucleosome antibody in SLE. In this study, raised anti-c1q antibodies and DsDna were independently associated with raised anti nucleosome antibody in SLE. Disclosure of Interest: None declared